EL CONOCIMIENTO PRIVADO DEL JUEZ COMO CAUSAL DEL IMPEDIMENTO Y/O RECUSACIÓN - Morales Cano, Ricardo A. (Revistas ICDP, 2026)
EL CONOCIMIENTO PRIVADO DEL JUEZ COMO CAUSAL DEL IMPEDIMENTO Y/O RECUSACIÓN